Structural basis of dimerization and nucleic acid binding of human DBHS proteins NONO and PSPC1. Issue 1 (14th December 2021) - Knott, Gavin J; Chong, Yee Seng; Passon, Daniel M; Liang, Xue-hai; Deplazes, Evelyne; Conte, Maria R; Marshall, Andrew C; Lee, Mihwa; Fox, Archa H; Bond, Charles S
Abstract: The Drosophila behaviour/human splicing (DBHS) proteins are a family of RNA/DNA binding cofactors liable for a range of cellular processes. DBHS proteins include the non-POU domain-containing octamer-binding protein (NONO) and paraspeckle protein component 1 (PSPC1), proteins capable of forming combinatorial dimers. Here, we describe the crystal structures of the human NONO and PSPC1 homodimers, representing uncharacterized DBHS dimerization states. The structures reveal a set of conserved contacts and structural plasticity within the dimerization interface that provide a rationale for dimer selectivity between DBHS paralogues. In addition, solution X-ray scattering and accompanying biochemical experiments describe a mechanism of cooperative RNA recognition by the NONO homodimer. Nucleic acid binding is reliant on RRM1, and appears to be affected by the orientation of RRM1, influenced by a newly identified 'β-clasp' structure. Our structures shed light on the molecular determinants for DBHS homo- and heterodimerization and provide a basis for understanding how DBHS proteins cooperatively recognize a broad spectrum of RNA targets. Graphical Abstract: